2023
DOI: 10.1051/e3sconf/202342904007
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction potential in the governor's office of West Sulawesi after the 2021 Mamuju-Majene earthquake

Sabra El Satilah,
Hary Christady Hardiyatmo,
Iman Satyarno

Abstract: The Governor's Office of West Sulawesi Province is close to an active fault, which triggers its vulnerability to seismic activity. The Mamuju Majene Earthquake destroyed the Governor's office building with a magnitude of Mw 6.2 in 2021. The geological conditions at the site are alluvial deposit formations. In addition to the geotechnical conditions, it has the characteristics of sandy soil with fine to medium gradations. Liquefaction causes a loss of soil strength and an increased pore water pressure caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A previous study indicated that the most vulnerable layers to liquefaction were found at BH-01 at depths of 12-18 meters and BH-03 at depths of 6-8 meters and 12-14 meters, with a medium to very high potential for liquefaction [5].…”
Section: Figure 3 Stratigraphy At the Research Locationmentioning
confidence: 92%
“…A previous study indicated that the most vulnerable layers to liquefaction were found at BH-01 at depths of 12-18 meters and BH-03 at depths of 6-8 meters and 12-14 meters, with a medium to very high potential for liquefaction [5].…”
Section: Figure 3 Stratigraphy At the Research Locationmentioning
confidence: 92%